Modulation of hide protein resistance to enzymatic hydrolysis by calcium ions: rational design of enzyme-assisted unhairing for high-quality leather production - Hao Liu; Xuyang Chen; Juntao Kang; Bi Shi; Yunhang Zeng (Collagen and Leather)
Abstract Enzymatic unhairing is an environmentally friendly and efficient method for leather processing. However, controlling protease hydrolysis remains challenging, leading to incomplete hair removal and potential grain damage. In modern leather manufacturing, the synergistic application of proteases, lime, and sulfide is increasingly employed to achieve satisfactory hair-saving unhairing performance. This study investigated the action mechanism of calcium ions in modulating the hydrolysis of hide proteins by proteases and proposed a balanced enzyme-assisted unhairing process. Enzymological and fluorescence spectroscopy analyses revealed that calcium ions could enhance the enzymatic resistance of hide proteins, including noncollagenous proteins and collagen, by binding to them. This enhancement in enzymatic resistance was more pronounced for globular proteins than for collagen fibers. In detail, following the addition of 20 g/L calcium ions, the hydrolytic activity of neutral and alkaline proteases decreased by 66.7% and 57.9% on bovine serum albumin, and by 40.7% and 48.1% on collagen fibers, respectively. Furthermore, the performance of the five unhairing processes was evaluated by varying the sequence of lime and protease application and type of protease used. Results indicated that while calcium ions exerted a protective effect on hide proteins and reduced damage to collagen fibers, they simultaneously hindered the removal of undesired noncollagenous proteins during unhairing. Consequently, the sequential application of lime followed by proteases resulted in the inadequate removal of interfibrillar substances, leading to unsatisfactory leather quality. Additionally, compared with an alkaline protease, a neutral protease was more easily inhibited under alkaline unhairing conditions, posed a lower risk of damage to the hide grain. Therefore, the neutral protease–lime–sodium sulfide unhairing process was chosen as the optimal strategy. This process involves the addition of neutral protease (50 U/g hide) for 60 min, followed by 1.0% lime for 90 min and 2.0% sodium sulfide for 90 min. These findings provide scientific insights for designing a controlled and efficient approach to enzyme-assisted unhairing processes. Graphical Abstract